2021
DOI: 10.14283/jpad.2021.8
|View full text |Cite
|
Sign up to set email alerts
|

Item-Level Investigation of Participant and Study Partner Report on the Cognitive Function Index From the A4 Study Screening Data

Abstract: Background: Greater subjective cognitive changes on the Cognitive Function Index (CFI) was previously found to be associated with elevated amyloid (Aß) status in participants screening for the A4 Study, reported by study partners and the participants themselves. While the total score on the CFI related to amyloid for both sources respectively, potential differences in the specific types of cognitive changes reported by either participants or their study partners was not investigated. Objectives: To determine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
27
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 19 publications
5
27
1
Order By: Relevance
“…That is, although models in the CN and the Dementia groups did not show significant effects, neither direct nor indirect, significant partial mediations were observed in the MCI group with EM. To begin with, increased discordance between the informant's and participant's complaints have already been observed in the literature, using raw complaint scores (Amariglio et al, 2021) as well as awareness indices as in our study (Folstein et al, 1975;Cacciamani et al, 2017Cacciamani et al, , 2020Hanseeuw et al, 2020;Vannini et al, 2020). In our study, only the MCI group demonstrated a significant relationship between amyloidosis, cognition and awareness, with EM partially mediating the relationship between amyloid and awareness.…”
Section: Discussionsupporting
confidence: 75%
“…That is, although models in the CN and the Dementia groups did not show significant effects, neither direct nor indirect, significant partial mediations were observed in the MCI group with EM. To begin with, increased discordance between the informant's and participant's complaints have already been observed in the literature, using raw complaint scores (Amariglio et al, 2021) as well as awareness indices as in our study (Folstein et al, 1975;Cacciamani et al, 2017Cacciamani et al, , 2020Hanseeuw et al, 2020;Vannini et al, 2020). In our study, only the MCI group demonstrated a significant relationship between amyloidosis, cognition and awareness, with EM partially mediating the relationship between amyloid and awareness.…”
Section: Discussionsupporting
confidence: 75%
“…Prior studies in CN participants have shown associations between amyloid burden and objective and subjective cognitive function 23–26 but only limited evidence for a relationship with IADL difficulties 16,17 . The current analyses demonstrated an association among IADL, amyloid burden, objective cognition, and subjective cognitive concerns.…”
Section: Discussioncontrasting
confidence: 48%
“…52 Greater reporting of CFI items was found to be associated with elevated amyloid levels in the brain. 53 The CFI demonstrated a similar effect size between amyloid beta groups as that of detailed neuropsychological testing in a recent study. 54 In the current study, we sought to build upon previous findings that SCC, measured by the CFI, was associated with concurrent and longitudinal cognitive performance in older adults without dementia 51,55 and aimed to examine the CFI's utility as a potential screening tool for MCI.…”
Section: Introductionsupporting
confidence: 51%